Advancing the Logic of Chemical Synthesis: C−H Activation as Strategic and Tactical Disconnections for C−C Bond Construction. Issue 29 (4th February 2021) - Lam, Nelson Y. S.; Wu, Kevin; Yu, Jin‐Quan
Abstract: The design of synthetic routes by retrosynthetic logic is decisively influenced by the transformations available. Transition‐metal‐catalyzed C−H activation has emerged as a powerful strategy for C−C bond formation, with myriad methods developed for diverse substrates and coupling partners. However, its uptake in total synthesis has been tepid, partially due to their apparent synthetic intractability, as well as a lack of comprehensive guidelines for implementation. This Review addresses these issues and offers a guide to identify retrosynthetic opportunities to generate C−C bonds by C−H activation processes. By comparing total syntheses accomplished using traditional approaches and recent C−H activation methods, this Review demonstrates how C−H activation enabled C−C bond construction has led to more efficient retrosynthetic strategies, as well as the execution of previously unattainable tactical maneuvers. Finally, shortcomings of existing processes are highlighted; this Review illustrates how some highlighted total syntheses can be further economized by adopting next‐generation ligand‐enabled approaches. Abstract : The advent of new synthetic methods has historically motivated the evolution of retrosynthetic logic. A significant recent advance is C−C bond formation enabled by C−H activation, but it has only seen modest application in synthesis. This Review compares traditional synthetic routes towards complex targets with reconceptualized ones utilizing C−H activation, highlighting the strategic advantages of this powerful approach.